The effect of β-glucan, carotenoids, oligosaccharides and anthocyanins on bacteria groups of excreta in broiler chickens - Csernus, Brigitta; Biró, Sándor; Babinszky, László; Stündl, László; Remenyik, Judit; Pesti-Asbóth, Georgina; Oláh, János; Czeglédi, Levente (Acta Agraria Debreceniensis, 2022)
This study was conducted to examine the effect of natural compounds, such as β-glucan, carotenoids, oligosaccharides, and anthocyanins in the diet on bacteria gropus of excreta in Ross 308 broiler chickens. Chickens were fed 5 diets: control (basal) diet, a diet supplemented by β-glucan at 0.05%, and diets supplemented by carotenoids, oligosaccharides, or anthocyanins at 0.5% of each compound. On experimental day 19, excreta were collected to determine the proportion of Lactobacillus, Bifidobacterium, Campylobacter, Clostridium, and Escherichia coli. Samples were collected aseptically and snap-frozen in liquid nitrogen. Bacterial DNA was isolated from samples, then polymerase chain reaction using primer pairs designed to the 16S rDNA of bacterial groups were applied to define the proportion of the mentioned bacteria. Another universal primer pair was used to amplify a region of 16S rDNA of all the examined bacteria. Proportion of each bacterial groups was determined relatively to the intensity of universal PCR product band by gel documenting system and ImageLab software. Based on the results, carotenoids and anthocyanins increased the proportion of Bifidobacterium, which might imply the beneficial effects of the mentioned compounds on the bacteria composition of excreta.